377PNGS in advanced NSCLC in a developing country: Ready for prime time?. (24th November 2019) - Amrith, B P; Sharma, M; Jain, P; Joga, S; Koyyala, V P B; Mehta, A; Batra, U
Abstract: Background: The increasing availability of targeted therapies has made genomic testing an integral part of management of patients with lung cancer. The guidelines are moving towards upfront molecular profiling of all advanced non-small cell lung cancers (NSCLC) with Next Generation Sequencing (NGS). Whether this translates into a clinically meaningful benefit in these patients, especially in a resource constrained country is yet to be determined. Methods: Patients with advanced adenocarcinoma of lung who underwent tissue NGS testing after a negative EGFR, ALK and ROS1 report between April 2017 and March 2019 were included. We retrospectively analyzed the testing outcomes and any change in clinical decision making after the NGS report in such patients. Results: Overall, NGS was done on tissue of 50 patients with advanced adenocarcinoma of lung. The median age was 58 years (range 27-82 years) and there were 31 males (58%). Most of the patients were never smokers 38(72%). The average turnaround time for the assay was 23 days (SD ± 15 days). One or more genomic alterations were found in 43 patients (86%) with most common genes affected being p53(43%), KRAS (19%), NOTCH1(13%), EGFR(6%), ROS1(4%), BRAF(8%) and HER2(8%). Seven (14%) of the patients were found to have mutations that were targetable by an FDA approved therapy and 9(18%) more patients had an off label available drug. So there was a potential for change of treatment in 16(32%) patients. Out of the 38(76%) patients who continued treatment at our institute, the NGS results led to a change in treatment in only 6(15%) patients. This was mostly due to limited availability of drugs, limited access to clinical trials and high cost of therapy. Conclusions: NGS is an important tool in the detection of targetable genetic alterations and results could potentially alter therapy. However, it is an expensive investigation and its clinical utility is questionable in a developing country like India. Single gene testing for common mutations is both rapid and cost-effective, and change in therapy after further NGS testing is possible in a very small percentage of patients. However, it may be considered after a detailed discussion with the patient in view of limited access to clinical trials or targeted therapies. Legal entity responsible for the study: Nil. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.